2021
DOI: 10.9734/ijpss/2021/v33i2430796
|View full text |Cite
|
Sign up to set email alerts
|

Standard Heterosis for Grain Yield and its Attributing Traits in Early Maturing Maize Hybrids

Abstract: The present study was conducted at the research farm of Dryland Agriculture Research Station, SKUAST-Kashmir during the kharif of 2019. Range of heterosis was calculated over standard check. The most desirable cross combinations viz., KDM-440 x KDM-914A (-5.879), KDM-440 x V-335 (-4.468), KDM-930 x V-351(-4.165), KDM-927A x V-335 (-3.986), CML-470 x KDM-914A (-3.808) for days to maturity, KDM-347 x V-351 (4.967) CML-470 x KDM-914A (4.610), CML-474 × V-351(-4.396), KDM-927 A x V-351 (-3.110), KDM-930 x V 335 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Most of the crosses had non-significant (p>0.05) SH for KRPE and KPR compared to the check (Table 3). Karim et al (2018) [7] ; Kumar et al (2021) [9] reported significant heterosis for grain yield and yield attributing traits which was in accordance with this study. Standard heterosis for thousand seed weight (TKW) ranged from -17.77% for L10xT4 to9.43%for L3xT2 than BH547.…”
Section: Standard Heterosissupporting
confidence: 89%
See 4 more Smart Citations
“…Most of the crosses had non-significant (p>0.05) SH for KRPE and KPR compared to the check (Table 3). Karim et al (2018) [7] ; Kumar et al (2021) [9] reported significant heterosis for grain yield and yield attributing traits which was in accordance with this study. Standard heterosis for thousand seed weight (TKW) ranged from -17.77% for L10xT4 to9.43%for L3xT2 than BH547.…”
Section: Standard Heterosissupporting
confidence: 89%
“…The presence of significant genotypic difference indicates existence of inherent genetic variation which could be exploited and makes selection possible for further maize breeding program. The depicted genetic variation among the tested genotypes for character of interest pave the way for breeder to carryout careful selection of the most desirable crosses and these finding is in agreement with Kumar et al (2021) [9] ; Yadesa (2022) [22] . 0.14 0.03 0.13 0.24 Whereas, HSARC= Haro Sabu Agricultural Research Centre, Rep= replication, Rep (block)= block within replication, **= significant difference at 0.01 probability level *= significant difference at 0.05 probability level and values with no asterisk are non-significant…”
Section: Analysis Of Variance (Anova)supporting
confidence: 85%
See 3 more Smart Citations